Hive‐Inspired Multifunctional Wood‐Nanotechnology‐Derived Membranes with a Double‐Layer Conductive Network Structure for Flexible Electronics. Issue 4 (23rd December 2021) - Zhang, Weiye; Wang, Beibei; Sun, Jingmeng; Li, Yanchen; Zhao, Junqi; Liu, Yi; Guo, Hongwu
Abstract: Next‐generation flexible electronics must achieve multifunctionality, environmental friendliness and antibacterial activity. Accordingly, organisms in nature are interconnected. Inspired by the honeycomb multilayer porous structure, a wood‐nanotechnology‐derived flexible membrane circuit is created to meet the abovementioned requirements. The flexible wood (FW) matrix is made of natural balsa wood that underwent a simple top‐down chemical treatment. The multiwalled carbon nanotube (MWCNT) acts as a "bridge" between the FW matrix with a porous array structure and the active material (silver nanoparticles (Ag NPs) and poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS). Due to the three‐dimensional porous microstructure and highly conductive surface inherited by the wood‐nanotechnology‐derived flexible membrane (FW/MWCNT/Ag/PEDOT:PSS), it shows a high area capacitance (266.7 mF cm −2 at 20 mV s −1 ) and a good long‐term cycling stability 84.3% capacitance retention after 5000 cycles at 5 mA cm −2 when used as a supercapacitor electrode. In addition, it shows an excellent specific electromagnetic shielding efficiency (up to 970 dB cm 2 g −1 ), proving its application potential in the field of electromagnetic shielding. Because of the biocidal property of Ag NPs, the FW/MWCNT/Ag/PEDOT:PSS shows a remarkable antibacterial effect on Escherichia coli and Staphylococcus aureus . This strategy provides a new opportunity for researchers to design biomass‐based integrated electronic materials. Abstract : A kind of wood‐nanotechnology‐derived flexible membrane with air permeability, biodegradability, and antibacterial properties was developed by the top‐down method. Due to its inherited three‐dimensional porous microstructure and highly conductive surface, it shows the potential application as supercapacitor electrodes and electromagnetic shielding material.